Single-phase mixed convection of developing and fully developed flow in smooth horizontal tubes in the laminar, transitional, quasi-turbulent and turbulent flow regimes - Meyer, Josua P. (University of Pretoria, 2018)
Thesis (PhD)--University of Pretoria, 2017.